Perbandingan Gaya Mengajar Komando Dan Gaya Mengajar Resiprokal Terhadap Hasil Belajar Gerak Dasar Pada Passing Bawah Dalam Permainan Bola Voli Pada Siswa Smp Negeri 3 Tondano - Orlince Mointing; Edita A.M. Pinangkaan; Cindy Ranty Rantung (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The research question in this study is: Is there a difference in the impact of implementing the command teaching method and the reciprocal teaching method on the development of basic underhand passing techniques in volleyball? This study aims to compare the effectiveness of the command teaching method and the reciprocal teaching method on the learning achievement of basic underhand passing techniques in volleyball among students at SMP Negeri 3 Tondano. The research approach applied was an experiment with a ‘Randomized Two Group Pre-test and Post-test Design’. The research sample included 20 students, divided into two groups: 10 students were taught using the command method and 10 students using the reciprocal method. The instrument used was an evaluation of basic underhand passing techniques in volleyball. Data analysis used normality, homogeneity, and t-tests with a significance level of α = 0.05. The results of the study show that tcount = 2.69 > ttable = 2.101, which means there is a significant difference. This analysis shows that there is a difference in the impact of the command teaching method and the reciprocal teaching method on the development of basic underhand passing skills in volleyball among students at SMP Negeri 3 Tondano. The conclusion of this research is that the command teaching method is more effective than the reciprocal teaching method in improving basic underhand passing skills in volleyball.